Da incredibile a credibile: strategie nazionali di promozione turistica in India - Maria Angelillo (Lingue Culture Mediazioni, 2015)
Tourism is at the top of Indian current Prime Minister Narendra Modi’s agenda: according to Bharatiya Janata Party’s manifesto, tourism can play a key role in India’s socio-economic progress. The country had last formulated a tourism policy in 2002, when the multimillion dollar nation branding campaign which received the name “Incredible India” was launched on an international level. The primary objective of this branding exercise was to create a distinctive identity for the country. Through the analysis of the campaign’s themes, the paper discusses its connection with orientalist imagery and colonial meanings as well as its effectiveness in promoting the Indian tourist industry. The article dwells on how the government’s campaign constructs the Indian difference for an imagined global audience. Questions of cultural othering, the role of colonialism, and contemporary neocolonial structures in relation to tourism promotion for India are discussed. In this paper it is argued that, if the government is serious about branding India with Narendra Modi’s much hyped 5 Ts, with tourism as a leading contributor, a new paradigm different from the “Incredible India” one may be necessary.